Le Sort des Contrats de Cautionnement et du Bail Commercial Lors des Opérations de Fusion - Arbaoui, Mounir (جامعة الحسن الأول - كلية العلوم القانونية والاقتصادية والاجتماعية - مختبر البحث قانون الأعمال, 2022)
Contracts are very important in that they are the lifeblood of the company and a determining factor in the decision to merge or not. Thus, the viability of the merger operation largely depends on the continuation of these contracts. Indeed, the automatic continuation applicable to all current contracts of the absorbed or merged company is justified by the specific nature of mergers, the major effect of which is the universal transmission of assets. However, the concept of intuitu personae characterizing some contracts prevents their automatic transfer. In this context, and faced with the silence of the legislator in the matter and the clash between contract law and company law, the continuation of commercial lease and surety contracts gives rise to thorny jurisprudential and doctrinal debates.
Keywords: العقود التجارية -- حوكمة الشركات -- الايجار التجاري